Available Micronutrient Status of Some Desert Soils Of Haryana - Singh, Kuldeep; Banerjee, N K (Annals of Arid Zone, 2016)
One hundred twentytwo surface soil samples belonging to desert soils of Haryana were analysed for available micronutrient cations and other soil properties. 1he soils were alkaline in reaction and low in organic carbon content. Average values for available Zn, Cu, Mn and Fe were 0.51,0.66,4.6 I and 2.45 ppm, respectively. Zn and Fe were negatively related with soil pH whereas significant and positive relationship was observed between available micronutrients and organic carbon. Soils were sufficient in Cu and marginal in Mn and Fe. Zinc was deficient in 91% soils and Zn application was a must for optimum crop yields in this region.